Influence of the types of grass of green roofs for the design of thermal comfort in buildings - Rodríguez, José (2022)
The main objective of the research was to study the effect of the Stenotaphrum secundatum and Zoysia japonica grasses on the higher and lower environment temperature and lower relative humidity; the secondary objective was to compare whether the Stenotaphrum secundatum grass has a greater impact on the environment parameters of comfort than the Zoysia japonica species. Six materials were used for the extensive green roof, each one forming a layer of the system, which were placed on the concrete slab and in an upward direction, including: PVC geomembrane, Polyester asphalt carpet, Pumice stone, Planar geodren, Prepared soil with guano, compost, muss, and Substrate. In order to make measurements of the higher and lower ambient temperature, a digital thermometer and lower relative humidity meter was used. Stenotaphrum secundatum and Zoysia japonica were used as grass species, as they were the most representative of the grasses used in extensive green roofs. The experimentation was carried out for 2 months from September to October of 2021, having built 3 modules of 1000x600mm roofs, including 1module of the concrete roof with ceramic covering and 2 modules of extensive green roof with two types of grass: Stenotaphrum secundatum and Zoysia japonica. The readings of the environment temperature and relative humidity of the higher and lower part were taken in six points of each module to have a greater number of representative measurements. The watering of the 2 green roof modules with grass was carried out twice a week, applying 5L of water per module. The results indicate that the Zoysia japonica grass is the one that presents a better behavior before the higher ambient temperature and that the Stenotaphrum secundatum grass behaves better before the lower ambient temperature and lower relative humidity. The conclusions indicate that the Stenotaphrum secundatum grass behaves better temperature and relative humidity; the two grass types exhibit different behavior.